Development of an end-effector to simulate the foot to ball interaction of an instep kick in soccer - Fraser, S.; Harland, A.; Donovan, P.; O'Shea, L. (Procedia Engineering, 2012)
Mechanical simulators are used to simplify the human kicking motion to provide repeatable contact between the endeffector and ball. The aim of the study was to examine the feasibility of using an ankle joint capable of simulating the plantar flexion deformation mechanism experienced by the human foot during the interaction with the soccer ball. A foot geometry was used to allow soccer boots to be fitted to the end-effector with a semi-bonded bush bearing to act as the ankle joint. The bearing provides a torsional resistance to radial loading, returning the foot to its starting position after the foot and ball impact. High speed video analysis using the GOM PONTOS system created three dimensional data points from markers placed on the end-effector, resulting in the relative rotations being quantified. Similarities between the plantar flexion mechanism in human kicking and the end-effector were observed, with a greater magnitude experienced by the end-effector. The end-effector provided repeatable foot rotations when struck with different initial foot velocities. The study concluded that a semi-bonded bush bearing can be used as an ankle joint to create repeatable contact between a foot geometry and a soccer ball. By increasing the bearing stiffness, the plantar flexion angular displacement can be reduced to levels experienced in human kicking.